1997
DOI: 10.1080/07448489709595597
|View full text |Cite
|
Sign up to set email alerts
|

How Sleep Deprivation Affects Psychological Variables Related to College Students' Cognitive Performance

Abstract: The effects of sleep deprivation on cognitive performance psychological variables related to cognitive performance were studied in 44 college students. Participants completed the Watson-Glaser Critical Thinking Appraisal after either 24 hours of sleep deprivation or approximately 8 hours of sleep. After completing the cognitive task, the participants completed 2 questionnaires, one assessing self-reported effort, concentration, and estimated performance, the other assessing off-task cognitions. As expected, sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(152 citation statements)
references
References 15 publications
9
125
2
Order By: Relevance
“…The study concluded that irregularity in the sleep-wake cycle and possible consequent sleep deprivation influence the academic performance of college students. A similar result was obtained by a study of 44 college students under two conditions, 24 hours of sleep deprivation or about 8 hours of sleep (Pilcher & Walters, 1997). The Watson-Glaser Thinking Skills Appraisal was used as a measure of cognition, in addition to a self-report measure of effort, concentration, and performance and another measure of off-task cognition.…”
Section: Other Possible Confounding Variablessupporting
confidence: 54%
“…The study concluded that irregularity in the sleep-wake cycle and possible consequent sleep deprivation influence the academic performance of college students. A similar result was obtained by a study of 44 college students under two conditions, 24 hours of sleep deprivation or about 8 hours of sleep (Pilcher & Walters, 1997). The Watson-Glaser Thinking Skills Appraisal was used as a measure of cognition, in addition to a self-report measure of effort, concentration, and performance and another measure of off-task cognition.…”
Section: Other Possible Confounding Variablessupporting
confidence: 54%
“…16,17 Sleep-deprived students usually perform significantly worse than those with normal sleep. 18,19 In addition, short sleep duration is associated with unhealthy risk behaviors, such as alcohol and tobacco use, which could increase the risk for developing hypertension, obesity, diabetes, hypercholesterolemia, and even mortality. [20][21][22][23][24][25] In contrast, long sleep duration can also be associated with negative outcome, such as increased risk of cardiovascular disease and cognitive impairment.…”
Section: Sleep Duration and Sleep Patterns In Chinese University Studmentioning
confidence: 99%
“…Another cause of not going to sleep until late is the use of central nervous system stimulants such as caffeine, caffeinated drinks, and caffeinated cocktails with alcohol. Furthermore, certain medical problems including obstructive sleep apnoea, chronic sleep deprivation, narcolepsy, cataplexy, depression, and idiopathic hypersomnia disrupt sleep (11,12). It is also understood that many students are themselves unaware of their sleep deprivation or poor sleep quality.…”
Section: Study Instrumentmentioning
confidence: 99%